Prevalence, risk factors, and prognosis of neonatal hypernatremic dehydration among full-term newborns: a systematic review - Maryam Zakerihamidi; Forough Rakhshanizadeh; Hassan Boskabadi (Hygeia Press di Corridori Marinella, 2023)
Introduction: Neonatal hypernatremic dehydration (NHD) is a major preventable problem associated with acute and chronic complications in neonates. Thus, the present study investigated the prevalence, risk factors, clinical signs, complications, and prognosis of NHD.  Materials and methods: In this study, we searched databases (PubMed, EMBASE and Google Scholar) for articles published until 2022. Keywords were: "hypernatremic dehydration", "neonatal", "risk factors", "prognosis", "complications", "prevalence", and "clinical signs". Persian- or English-language articles with sufficient data on NHD were included in the study. Finally, 24 relevant articles were examined.  Results: Significant weight loss, delayed first breastfeeding, breastfeeding frequency, early discharge, use of sugar water and manna, low frequency of urination and defecation, summer season, use of heaters, and late referral age are NHD risk factors. Jaundice, hyperthermia, lethargy, poor feeding, restlessness, decreased skin turgor, and seizure are the clinical signs of NHD. Laboratory findings include increased urea, creatinine, sugar, and sodium levels. Renal problems (azotemia, high creatinine, renal insufficiency, and stones), neurological complications (cerebral edema, seizure, loss of consciousness, cerebral hemorrhage, developmental delay, and hearing impairment), coagulopathy, and thrombocytopenia are the complications of NHD.  Conclusion: NHD and its complications could be prevented by prompt and appropriate prevention of risk factors, early detection based on clinical signs, and appropriate treatment.